First, we can factor out a 2 from the equation:
2(x²-4x-12)=0
Divide by 2 to simplify
x²-4x-12=0
Now to factor, we must find what multiplies to -12, but adds to get -4. I can tell you know, the numbers are -6 and 2 (Through time you will learn to get faster with factoring)
Now we set it up as so:
(x-6)(x+2) = 0
Now to find the solutions, you must find how to get each set of parenthesis equal to 0.
x-6=0
x=6 is a solution
x+2=0
x=-2 is a solution as well.
So your answer is x=6 and -2 (Answer Choice C)
I Hope this Helps!
-Sinnamin